Peningkatan Pengetahuan Kader Posyandu tentang Hak dan Kewajiban Ibu Hamil dan pemanfaatan aplikasi “sayang bunda” - Dwi Erawati, Ambar; Chusnul Zulaika; Mona Tiorina Manurung (Pusat Riset dan Inovasi Nasional, 2022)
Telemedicine is an alternative health service facility that can help reduce disease transmission. The Semarang City Government issued a “darling mother” application to help pregnant women consult and assist cadres in screening. However, the